Vulnerability of mineral-organic associations in the rhizosphere - Bölscher, Tobias ; 0000-0001-5305-0616; Cardon, Zoe G.; Garcia Arredondo, Mariela; Grand, Stéphanie; Griffen, Gabriella; Hestrin, Rachel; Imboden, Josephine; Jamoteau, Floriane; Lacroix, Emily M.; Pérez Castro, Sherlynette; Persson, Per; Riley, William J.; et al. (Nature Communications, 2025)
The majority of soil carbon (C) is stored in organic matter associated with reactive minerals. These mineral-organic associations (MOAs) inhibit microbial and enzymatic access to organic matter, suggesting that organic C within MOAs is resistant to decomposition. However, plant roots and rhizosphere microbes are known to transform minerals through dissolution and exchange reactions, implying that MOAs in the rhizosphere can be dynamic. Here we identify key drivers, mechanisms, and controls of MOA disruption in the rhizosphere and present a new conceptual framework for the vulnerability of soil C within MOAs. We introduce a vulnerability spectrum that highlights how MOAs characteristic of certain ecosystems are particularly susceptible to specific root-driven disruption mechanisms. This vulnerability spectrum provides a framework for critically assessing the importance of MOA disruption mechanisms at the ecosystem scale. Comprehensive representation of not only root-driven MOA formation, but also disruption, will improve model projections of soil C-climate feedbacks and guide the development of more effective soil C management strategies.
Publisher Copyright: © The Author(s) 2025.